Open Educational Resources: evolution and models - Mª Paz Trillo Miravalles (FahrenHouse, 2012)
With the revolution in Information Technologies and Communication, a new thinking emerges about the use of these means from different fields. This article presents the evolution and prospect of technologies from the socioeducational field, it shows different movements emerged on European and international level. It analyses the Open Educational Resources (OER) understood as new resources owing to the fact that they are offered free of charge to the whole society, they manage to share, adapt and use the knowledge.